2013
DOI: 10.1108/jqme-08-2013-0054
|View full text |Cite
|
Sign up to set email alerts
|

Profitable working capital management in industrial maintenance companies

Abstract: Purpose -The purpose of this paper is to analyze the impact of working capital management on profitability in industrial maintenance service companies.Design/methodology/approach -Analytical modeling has been used as the research method. Finnish industrial maintenance companies have been analyzed on the basis of their financial statements.Findings -We reveal a significant negative correlation between the cycle times of operational working capital and the return on investment of industrial maintenance companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…They suggested that managers could add value to growth for business owners by cutting accounts receivable days down to 30. With panel data analysis, Tauringana and Afrifa (2013) displayed the importance of management of accounts payable and receivable for the profitability of SMEs, while on the other hand, Marttonen et al (2013) used a flexible asset management tool to put forward the existence of a negative correlation between the cycle times of operational working capital and return on investment for industrial maintenance service companies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They suggested that managers could add value to growth for business owners by cutting accounts receivable days down to 30. With panel data analysis, Tauringana and Afrifa (2013) displayed the importance of management of accounts payable and receivable for the profitability of SMEs, while on the other hand, Marttonen et al (2013) used a flexible asset management tool to put forward the existence of a negative correlation between the cycle times of operational working capital and return on investment for industrial maintenance service companies.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The management of operational working capital as part of SCF requires balancing the reduction of capital that is already tied up, which increases profitability, and minimizing risks caused by a too-small amount of operational working capital (Marttonen et al, 2013). When financing and investing in working capital, actors tend to subscribe to one of three approaches: aggressive, moderate, or conservative (Brigham et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Particularly in substantial undertakings the CCC can't be abbreviated. Be that as it may, the expansive undertakings appear to have an upper hand over the SME(s) because of lower settled resources proportions (Marttonen, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%